2011
DOI: 10.1103/physrevlett.106.220501
|View full text |Cite
|
Sign up to set email alerts
|

Fully Distrustful Quantum Bit Commitment and Coin Flipping

Abstract: In the distrustful quantum cryptography model the parties have conflicting interests and do not trust one another. Nevertheless, they trust the quantum devices in their labs. The aim of the device-independent approach to cryptography is to do away with the latter assumption, and, consequently, significantly increase security. It is an open question whether the scope of this approach also extends to protocols in the distrustful cryptography model, thereby rendering them "fully" distrustful. In this Letter, we s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…During the preparation of this work, other groups have shown that our protocol can be modified to reduce the bias slightly2324. Alternatively, a device-independent and loss-tolerant protocol, having a bias lower than our protocol, was recently proposed25. Whether a loss-tolerant protocol can asymptotically reach the optimal bound for strong coin flipping9 is still an open question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the preparation of this work, other groups have shown that our protocol can be modified to reduce the bias slightly2324. Alternatively, a device-independent and loss-tolerant protocol, having a bias lower than our protocol, was recently proposed25. Whether a loss-tolerant protocol can asymptotically reach the optimal bound for strong coin flipping9 is still an open question.…”
Section: Discussionmentioning
confidence: 99%
“…We note that, in principle, this assumption could be relaxed by using a device-independent quantum coin flipping protocol such as the one proposed recently in ref. 25.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming that the devices carry at least some memory of past interactions is an extremely realistic assumption due to technical limitations, even if Alice and Bob prepare their own trusted, but imperfect, devices, highlighting the extreme importance of such analyses for the implementation of device independent QKD. In contrast, relatively little is known about device independence outside the realm of QKD [12][13][14][15].Conference key agreement [16,17] (CKA or N-CKA) is the task of distributing a secret key among N parties. In order to achieve this goal, one could make use of N −1 individual QKD protocols to distribute N − 1 different keys between one of the parties (Alice) and the others (Bob 1 , .…”
mentioning
confidence: 99%
“…uses only the properties of quantum information, an increasingly long list of applications illustrate the added cryptographic power of the relativistic no-signalling principle, either alone (e.g 78910111213141516171819202122232425262728293031323334353637…”
mentioning
confidence: 99%